The Model of Global Marketing Strategy and Performance - Sudarso, Andriasan; Sofiati, Nunung Ayu (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The aim of this research is to examine the impact of global marketing strategy on the overall performance of Sharia Apartment Developer in Asia. The participants in this study consisted of all employees working for the Sharia Apartment Developer, totaling 30 developers across three countries (Hongkong, Singapore, and Indonesia). The data collected for this study is quantitative in nature, meaning it is presented in numerical form. This data provides insight into the specific values and variables it represents. The analysis method employed in this study encompasses descriptive analysis and verification analysis. The utilization of global marketing strategies has been shown to have a favorable and noteworthy impact on the overall performance of global marketing. These strategies also hold implications for Sharia Apartment Developers, as they are based on various indicators that highlight the potential strengths and opportunities for these developers in the future. To successfully implement a global marketing strategy, it is crucial to employ an intensive approach that aims at penetrating a wider market. This can be achieved through robust advertising campaigns across print and electronic media, personalized sales calls, enticing sales promotions, and generating publicity. The enhancement of the market (market development) can be achieved through enhanced collaboration. Similarly, product development can be attained by incorporating cutting-edge technology into the facilities. The future implications of the global marketing strategy for a Sharia apartment developer are intertwined with the global marketing mix, specifically focusing on product improvement through renovation and modernization of amenities. This will enable the sharia apartment developer to better compete in the market. Moreover, its advantageous location near public amenities adds to its strategic value. To further promote their offerings, it would be beneficial to diversify promotional media and forge more vigorous alliances with other entities. Prices have a tendency to be quite adaptable. There is a regular practice of running promotions to remind consumers of the current offerings, including both existing and new products, as well as any adjustments in pricing that may have taken place. In addition, every morning there is a customary briefing where one can peruse the latest information. By fostering increased collaboration with other entities, it is possible to enhance cooperation and achieve mutually beneficial outcomes.